Numerical Investigations of Combustion - Afonso, Alexandre M.; Resende, Pedro; Ayoobi, Mohsen (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue will highlight the latest advances in numerical modeling of combustion-related applications. With the recent advancements in computational capacities and the widespread use of simulations in engineering problems, numerical methods are becoming increasingly important to improve existing models and develop new models that can help researchers to better understand the underlying mechanisms of combustion, their interaction with other physical phenomena, such as turbulence, and their impacts on the performance of related applications at both fundamental and practical levels.